Group Well-Child Care: An Analysis of Cost. (April 2014) - Yoshida, Hiromi; Fenick, Ada M.; Rosenthal, Marjorie S.
Objective . To determine if group well-child visits (WCV) can be cost neutral compared with individual WCV by varying health care providers, group size, and physician salary. Method . We created 6 economic models to evaluate the costs of WCV: 3 for individual WCV delivered by (1) advanced practice registered nurse (APRN), (2) resident, and (3) attending and 3 for group WCV delivered by (4) APRN with a nurse and social worker; (5) resident with an attending, nurse, and child life specialist; and (6)attending with a nurse. For group WCV, we performed sensitivity analyses on group size and duration of provider participation. Results . We achieved cost-neutrality at 4 families in the APRN group WCV model; at 3, 4, 5, and 6 families in the resident model with 30, 45, 60, and 90 minutes of attending supervision, respectively; and at 4 and 5 families in the low and high attending salary model, respectively. Conclusion . Group WCV can be delivered in a cost-neutral manner by optimizing group size and provider participation.